The Conflict of Private International Law in Determining Child Custody After Cross-Border Divorce: A Case Study in Indonesia - Riyawi, Mohd Rafi; Makruflis, Muhammad (Raudhah Publisher, 2024)
This article explores the conflict of private international law in determining child custody following cross-border divorces, focusing on a case study in Indonesia. In an increasingly globalized world, marriages and divorces often involve parties from different nationalities, leading to legal complexities in custody disputes. The aim of this study is to analyze the challenges that arise in the application of Indonesian law when adjudicating custody rights in cross-border divorce cases, particularly when different legal systems are involved. Using a qualitative research method, this study employs a literature review and library research to examine relevant legal frameworks, including Indonesian domestic laws, international treaties, and comparative legal principles. The findings suggest that while Indonesia has made strides in addressing cross-border custody issues, significant challenges remain due to the lack of comprehensive private international law regulations. Additionally, conflicts arise when attempting to reconcile Indonesian legal principles with international norms, such as those related to the Hague Convention on International Child Abduction. This research contributes to the ongoing discussion on improving legal mechanisms for cross-border custody disputes and emphasizes the importance of harmonizing domestic laws with international legal standards to ensure the best interests of the child are upheld.